As Tecnologias de Informação e Comunicação e a mediação docente - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
This study, adopting a qualitative approach, addresses technologies in education, from the following question: how the teacher's mediation in the use of Information and Communication Technologies (ICT) occurs? From this question, it was intended to understand how the teacher's mediation occurs when ICT is used in the classroom. Therefore, we sought a closer understanding of teaching mediation and ICT, through a case study in a public school in the early years, in the city of Valparaíso de Goiás. For the study, statistical and educational data was collected from the Basic Education, from the State of Goiás and from the studied city. The teachers, subjects of the research, were characterized and their reports were collected. The semi-structured interviews and observations conducted at the school helped confirm the actions of teachers, which were analysed through the grouping of ideas and expressions of the study. In light of Vygotsky (1989), Lenoir (2011), D'Avila (2002) and Toschi (2010) it was sought to analyse the meaning that mediation assumes in the subject / object of knowledge. Taking into consideration the technology and its historicity, the proposed reflections were guided by Vargas (1999), Cardoso (1999), Dowbor (2001) and Grinspun (1999). The text proposes an understanding of the teacher function, based on ideas from Nóvoa (1992), Libâneo (1994, 2011), among other scholars, and highlights the didactic mediation as a proposal to be considered by the teacher in order to contribute to a practice in which the student is led to actively participate in the teaching and learning process in an active and effective way. The results cannot inform that ICT contribute to teaching mediation in the early years. The difficulties faced by teachers in their daily lives prevent the realization of several planned activities and do not fostering the engagement of students in the work performed.
Keywords: As Tecnologias de informação e comunicação e a mediação docente; Tecnologia da Informação e Comunicação - TIC na educação; Teconologia da Informação e Comunicação e mediação docente; Cognitive mediation and didactic mediation; Information and Communication Technology in education; Information and Communication Technology and teaching mediation; CIENCIAS HUMANAS::EDUCACAO